Analysis of the Effect of Regional Financial Performance on Regional Inequality in Java, Sumatra and Sulawesi Provinces in 2016-2022 - Putri Miswa Laila Kumara; Yuni Prihadi Utomo (International Journal of Economics Development Research (IJEDR), 2024)
This study aims to measure the direction and magnitude of the influence of Regional Financial Independence Ratio (DDF), Effectiveness Ratio of Local Revenue (REPAD), Regional Expenditure Compatibility Ratio (RKBD), GRDP Per Capita (PDRBPKP) and Population Density (KPD) on Regional Inequality in the Provinces of Sumatra, Java and Sulawesi in 2016-2022. This research uses panel data analysis. The results found that the Fixed Effects Model (FEM) was selected as the best estimation model, as this model has high predictive power. Partially, the variables Regional Financial Independence Ratio (DDF), Effectiveness Ratio of Local Revenue (REPAD) and GRDP Per Capita (PDRBPKP) affect the variable Regional Inequality in the provinces of Sumatra, Java and Sulawesi in 2016-2022. A high Regional Financial Independence Ratio indicates efficient resource allocation and regional economic sectors that effectively reduce regional inequality. An increase in the Efficiency of Regional Local Revenues, which are not always evenly distributed, can increase inter-regional inequality. A high GRDP per capita does not always reflect an equitable distribution of wealth in society, which can increase interregional inequality. Policies are needed to strengthen regional autonomy and optimize financial management.